Women with Special Educational Needs. Policies & ICT for Integration & Equality - Bakola , Lizeta; Chaidi, Irene; Drigas, Athanasios; Skianis, Charalabos; Karagiannidis, Charalampos (Technium Social Sciences Journal, 2022)
Gender equality is a demand in all societies and is a key goal of all of us, as well as the integration of people with disabilities and especially women. This article reports on the prevailing situation of women with disabilities in society, how to deal with them and how to eliminate their exclusion and accept them as equal citizens in society.